Menghitung Biaya Psikologis Litigasi Perceraian Bagi Perempuan Penggugat - Haiyun Nisa; Koentjoro; Khoiruddin Nasution (Asosiasi Psikologi Forensik (Apsifor), 2023)
Litigation is the process of resolving several dispute cases through the courts, including divorce cases. The divorce litigation process is a series of processes for resolving the breakdown of the husband and wife's marital relationship, which is determined by a permanent legal decision. The Supreme Court has issued Regulation Number 3/2017 on Guidelines for Adjudicating Women Against the Law, but there are still several problems experienced by women in the legal process. As plaintiffs, women must pay several court fees when filing a divorce case through court. Apart from a certain amount of legal costs, it turns out that women also incur significant psychological costs when participating in the litigation process. How and how much psychological cost do women incur? This research explores women’s experiences suing for divorce regarding the psychological costs incurred during the litigation process. Five female plaintiffs participated in semi-structured interviews. The findings of this study indicate that the psychological costs incurred during the divorce litigation process include ignorance of the divorce legal process, anxiety about facing the trial process in court, fear of facing the husband during the trial in court, and emotional and relational difficulties. The psychological costs of litigation can affect the psychological well-being of women who file for divorce, so efforts are needed to minimize the psychological costs of the litigation process with the involvement and collaboration of all parties. It is hoped that the results of this research can help policymakers design litigation processes that minimize high psychological costs.